Energy-saving polyester PET sheet and production method thereof
The PET sheet composition with a main body and reinforcement layer, using dioctyl phthalate and polyethylene wax, and MBS copolymer, addresses energy inefficiencies in PET sheet production by enabling low-temperature processing, improving fluidity and strength, and ensuring weather resistance.
Patent Information
- Application Number
- CN202411321341.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing PET sheet production processes are energy-inefficient due to high temperatures required for material fluidity, leading to significant energy waste.
A PET sheet composition with a main body layer and reinforcement layer, incorporating dioctyl phthalate and polyethylene wax to reduce glass transition temperature, and MBS copolymer and glass fibers for improved fluidity and strength, along with a UV coating for weather resistance, combined with a low-temperature production method.
Reduces energy consumption by allowing lower production temperatures while maintaining mechanical and weather-resistant properties, enhancing the PET sheet's performance and appearance.
Smart Images

Figure CN119239091A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PET sheets, in particular to an energy-saving polyester PET sheet and a production method. Background Art
[0002] PET sheet is a plastic sheet made of polyethylene terephthalate (PET). It has excellent physical and chemical properties and is widely used in packaging, construction, electronics and other fields. PET sheet has good mechanical strength and rigidity, can withstand large loads, and has good wear resistance and impact resistance, suitable for various application scenarios. At the same time, PET sheet has good tolerance to most chemicals, including acids, alkalis and organic solvents.
[0003] The production process of PET sheets mainly includes ① raw material preparation, using polyethylene terephthalate (PET) particles as the main raw material; additives: adding plasticizers, stabilizers, masterbatches, etc. as needed, these additives can improve the processing performance, stability and appearance of PET.
[0004] ② Extrusion molding: the dried PET raw materials and additives are heated and melted through a screw extruder. The temperature zone of the extruder is generally set between 260-280℃, and the specific temperature depends on the raw materials and formula.
[0005] Among them, the PET in the molten state passes through a filter to remove impurities and is evenly mixed in the extruder to ensure the homogeneity of the material.
[0006] ③ Forming and cooling: the molten PET is extruded from the T-die to form the initial sheet. The thickness of the sheet is determined by the opening gap of the die. The sheet is cooled and shaped by a series of cooling rollers. The cooling rollers are generally set to water cooling, and the roller temperature is controlled between 20-40°C to ensure that the sheet cools quickly without deformation.
[0007] ④ Biaxial stretching: In order to improve the mechanical properties and transparency of PET sheets, biaxial stretching process can be carried out. The sheets are stretched longitudinally and transversely at a certain temperature (80-120℃), and the stretching ratio is usually between 3:1 and 4:1; Heat setting: After stretching, the sheets are subjected to heat setting process to eliminate internal stress and improve dimensional stability. The setting temperature is generally controlled at 150-180℃.
[0008] ⑤Surface treatment: according to application requirements, the surface of the sheet is treated with anti-fog, anti-static, anti-ultraviolet and other treatments. Surface treatment can be carried out by coating or co-extrusion; Surface finish control: further polishing or treatment to achieve the required surface gloss and smoothness.
[0009] ⑥ Curling and cutting The cooled sheet is rolled into a roll by a curling device for easy transportation and storage; according to customer needs, the sheet can be cut into sheets or plates of different specifications.
[0010] In order to meet the convenience of the molding process during the production process, the raw materials need to be heated and melted to 260-280°C. At such a temperature, the raw materials have better fluidity, which is convenient for the molding of the materials and improves the uniformity of the thickness of the materials. Similarly, higher process temperatures will also cause waste of PET sheets during the production process. Although there are many heat recovery methods and devices in the prior art, they are still plagued by the problem of recovery efficiency, resulting in a large amount of energy waste. Therefore, there is an urgent need for a PET sheet that can reduce process energy consumption. Summary of the invention
[0011] In order to make up for the deficiencies of the prior art, the present invention proposes an energy-saving polyester PET sheet and a production method. The present invention is mainly used to solve the problem of excessive energy consumption in the production process of the existing PET sheet.
[0012] The technical solution adopted by the present invention to solve the technical problem is: an energy-saving polyester PET sheet, characterized in that: it includes a main body layer, a reinforcement layer is arranged between two main body layers, and the reinforcement layer is bonded to the main body layer;
[0013] The main body layer is made of the following raw materials in parts by weight: 80-100 parts of PET resin, 2-5 parts of dioctyl phthalate, 0.5-1 part of polyethylene wax, 0.1-0.3 parts of hindered phenol antioxidant and 0.2-0.5 parts of zinc stearate.
[0014] Since the plasticizer (dioctyl phthalate) has a small molecule, it can be inserted between PET molecular chains to increase the freedom of movement between the molecular chains, thereby lowering the glass transition temperature of the PET resin. At the same time, the plasticizer inserted between the molecular chains can reduce the van der Waals force and other secondary bond forces between the molecular chains, reduce the mutual attraction between the molecular chains, and make the molecular chains easier to move. In the production process of PET sheets, even if the temperature of PET in a molten state is reduced, the PET melt can have better fluidity, thereby realizing low-temperature production of PET sheets, thereby reducing energy loss in its production process and improving the energy saving of the production process;
[0015] Preferably, the main body layer further comprises 3-8 parts by weight of methyl methacrylate-butadiene-styrene copolymer.
[0016] The butadiene component in the MBS copolymer is elastic and can effectively absorb impact energy, thus improving the impact resistance of the material. This toughening effect allows the material to maintain good toughness even at low temperatures, reducing the risk of brittle fracture; MBS can improve the surface gloss and transparency of the material, improve the appearance quality, and make the product more competitive in the market. Especially in applications requiring high transparency and high gloss, such as transparent packaging and optical components, the addition of MBS has a significant effect.
[0017] Preferably, the reinforcement layer is made of the following raw materials in parts by weight: 80-100 parts of PET resin, 2-3 parts of glass fiber, 1-2 parts of nano-silicon dioxide and 0.5-0.8 parts of polycarbonate.
[0018] The glass fibers dispersed in the PET matrix can share the external load and reduce the stress concentration of the matrix, thereby improving the strength and rigidity of the composite material; at the same time, good interface bonding can effectively transfer stress, so that the glass fibers and the PET matrix can bear the load together and enhance the overall performance of the material.
[0019] Preferably, the PET sheet further comprises a UV coating, which is disposed on the surface of the body layer and has a thickness of 0.05-0.1 mm.
[0020] During the preparation of the main layer, plasticizers and flow modifiers are added, which will reduce the weather resistance of PET, making the PET sheet prone to aging and discoloration when used outdoors. Therefore, applying a layer of UV coating on the surface of the sheet can increase the weather resistance of the PET sheet when used outdoors, improve the energy saving of the product while ensuring its weather resistance, thereby improving the application value of the product.
[0021] The present invention also provides a method for producing energy-saving polyester PET sheets, comprising the following steps:
[0022] S1: Preparation of the bulk layer: half of the PET resin particles in the designed ratio are mixed with dioctyl phthalate and polyethylene wax, and heated to 220-230°C to melt them; then the remaining PET resin particles are added while stirring until they are all melted; then methyl methacrylate-butadiene-styrene copolymer, hindered phenol antioxidant and zinc stearate are added and mixed evenly to obtain a molten body of the bulk layer;
[0023] S2: Preparation of reinforcing layer: All the designed amount of PET resin particles are heated to 220-230°C to make them in a molten state, and then nano-silicon dioxide is added thereto. After stirring evenly, glass fiber is added thereto and stirred evenly, and then polycarbonate is added and stirred for 10-20 seconds to obtain a molten body of the reinforcing layer;
[0024] S3: extrusion molding, the molten body layer and the reinforcing layer are respectively put into the extruder, and the extruder is operated to extrude them into sheets, and then cooled to form sheet-like semi-finished products;
[0025] S4: bonding and molding; the temperature of the main body layer to be extruded is reduced to 60-80 degrees Celsius, and the temperature of the reinforcement layer to be extruded is reduced to 100-120 degrees Celsius, and then the interface adhesive is sprayed on the surface of one side of the reinforcement layer, and then the main body layer is adhered to the reinforcement layer, and then the pressure is maintained for 30 minutes, and the spraying and bonding processes are repeated to complete the bonding of the main body layer on the other side;
[0026] S5: Surface treatment: anti-aging treatment is performed on the surface of the sheet after the main layer and the reinforcement layer are adhered.
[0027] Preferably, a method for producing energy-saving polyester PET sheets further comprises the following steps:
[0028] Dry the raw materials, spread the PET particles evenly inside the vacuum dryer, and dry them at 120℃ for 30 minutes;
[0029] Raw material testing: take samples of the dried raw materials and use a moisture tester to test their moisture content. If the moisture content does not exceed 0.005%, it can be put into use, otherwise it will be dried again.
[0030] Raw materials are removed from the environment by putting the raw materials with qualified moisture content into the electrostatic dust removal equipment to remove the tiny dust impurities on the surface and complete the pretreatment of the PET granule raw materials.
[0031] Polyester materials such as PET are prone to hydrolysis during high-temperature processing, which leads to molecular chain breakage, reduced molecular weight, and thus affects the quality of PET finished products. Therefore, by removing moisture, hydrolysis can be prevented, the molecular weight of the material can be maintained, and the mechanical properties and chemical stability of the material can be ensured. Secondly, moisture will turn into steam at high temperatures, affecting the fluidity and uniformity of the melt. After dehydration, the raw materials in the molten state have better fluidity, which helps to improve processing performance and product quality. Furthermore, moisture will form bubbles during processing, resulting in defects on the surface of the finished product such as pores and flow marks. Removing moisture can avoid these defects, ensure the smoothness and uniformity of the finished product surface, and improve the appearance quality.
[0032] Preferably, the anti-aging treatment of the sheet surface comprises the following steps:
[0033] Surface roughening: use a grinding head with a mesh size of 800 or above to grind the PET surface, and then clean the surface;
[0034] Spray the UV layer, evenly apply the UV coating on the polished sheet surface, and then wait for the sheet surface to dry naturally;
[0035] Apply UV coating by brushing. After the surface of the sheet is dry, apply UV coating by brushing on it;
[0036] Curing treatment uses ultraviolet rays to irradiate the coating so that it cures quickly to form an anti-aging layer on the surface.
[0037] Since the surface smoothness of the PET sheet will decrease after grinding, spraying often cannot solve the problem of surface smoothness, and directly applying the UV coating by spreading often leads to low bonding strength. Therefore, spraying is first used for primer so that a small amount of UV material is combined with the main layer, and then coating is used to solve the problem of surface smoothness, thereby improving the quality of the product.
[0038] Preferably, in step S4, before the main layer and the reinforcement layer are bonded together, a 200-mesh grinding head is used to grind the surface where the main layer and the reinforcement layer are bonded; and the thickness of the interface adhesive is not less than 2 mm.
[0039] By grinding the bonding surface, the bonding area of the bonding surface can be increased, thereby increasing the bonding strength and improving the integrity of the produced sheet. After measurement, the difference between the protrusions and grooves on the surface after grinding with a 200-mesh grinding head is generally 0.4-1mm. By controlling the thickness of the interface glue, it can be ensured that the main layer and the reinforcement layer after bonding can achieve better bonding strength and better flatness.
[0040] The beneficial effects of the present invention are as follows:
[0041] 1. In the present invention, since the molecule of the plasticizer (dioctyl phthalate) is relatively small, it can be inserted between the PET molecular chains to increase the freedom of movement between the molecular chains, thereby reducing the glass transition temperature of the PET resin. At the same time, the plasticizer is inserted between the molecular chains, which can reduce the van der Waals force and other secondary bond forces between the molecular chains, reduce the mutual attraction between the molecular chains, and make the molecular chains easier to move. In addition, in the production process of the PET sheet, even if the temperature of the PET in the molten state is reduced, the PET melt can have good fluidity, thereby realizing the low-temperature production of the PET sheet, thereby reducing the energy loss in the production process and improving the energy saving of the production process;
[0042] At the same time, the polyethylene wax in the component has excellent lubricating effect in the molten state, and can form a lubricating layer between PET molecular chains to reduce internal friction; the lubricating layer reduces the friction resistance between the molecular chains, so that the PET melt has better fluidity at a lower temperature; and the polyethylene wax can effectively reduce the viscosity of the PET melt, promote the slippage of the molecular chains, and improve the fluidity, further improving the fluidity of the PET melt, and can further improve the quality of PET sheets produced under low temperature conditions.
[0043] 2. The methyl methacrylate-butadiene-styrene copolymer in the present invention has a lower melt viscosity, and can reduce the viscosity of the entire melt after mixing with PET, thereby improving fluidity; secondly, the molecular structure of MBS contains a flexible butadiene part, which increases the flexibility of the molecular chain of the blend, making PET easier to flow at a lower temperature; furthermore, MBS, as a modifier, forms a blending system with good miscibility with PET, and the modified material has better processing properties, thereby being able to enhance the low-temperature fluidity of the PET melt, further reduce the temperature in its production process, and thereby improve the energy saving of its production.
[0044] 3. In the present invention, since the molecules of the plasticizer (dioctyl phthalate) are relatively small, they can be inserted between the PET molecular chains to increase the freedom of movement between the molecular chains, thereby reducing the glass transition temperature of the PET resin. At the same time, the plasticizer is inserted between the molecular chains, which can reduce the van der Waals force and other secondary bond forces between the molecular chains, reduce the mutual attraction between the molecular chains, and make the molecular chains easier to move. In addition, in the production process of the PET sheet, even if the temperature of the PET in the molten state is reduced, the PET melt can have better fluidity, thereby realizing the low-temperature production of the PET sheet, thereby reducing the energy loss in the production process and improving the energy saving of the production process;
[0045] At the same time, the polyethylene wax in the component has excellent lubricating effect in the molten state, and can form a lubricating layer between PET molecular chains to reduce internal friction; the lubricating layer reduces the friction resistance between the molecular chains, so that the PET melt has better fluidity at a lower temperature; and the polyethylene wax can effectively reduce the viscosity of the PET melt, promote the slippage of the molecular chains, and improve the fluidity, further improving the fluidity of the PET melt, and can further improve the quality of PET sheets produced under low temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The present invention will be further described below in conjunction with the accompanying drawings.
[0047] Figure 1 Schematic diagram of the cross section of the energy-saving PET sheet of the present invention;
[0048] Figure 2It is a flowchart of the method for producing energy-saving polyester PET sheets in the present invention;
[0049] In the figure: 1. Main body layer; 2. Reinforcement layer; 3. UV coating. DETAILED DESCRIPTION
[0050] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0051] like Figure 1 As shown, an energy-saving polyester PET sheet comprises a main body layer 1, a reinforcing layer 2 is arranged between two main body layers 1, and the reinforcing layer 2 is bonded to the main body layer 1;
[0052] The main body layer 1 is made of the following raw materials in parts by weight: 80-100 parts of PET resin, 2-5 parts of dioctyl phthalate, 0.5-1 parts of polyethylene wax, 0.1-0.3 parts of hindered phenol antioxidant and 0.2-0.5 parts of zinc stearate.
[0053] During operation, since the plasticizer (dioctyl phthalate) has a small molecule, it can be inserted between PET molecular chains to increase the freedom of movement between the molecular chains, thereby reducing the glass transition temperature of the PET resin. At the same time, the plasticizer is inserted between the molecular chains, which can reduce the van der Waals force and other secondary bond forces between the molecular chains, reduce the mutual attraction between the molecular chains, and make the molecular chains easier to move. In addition, during the production process of PET sheets, even if the temperature of PET in a molten state is reduced, the PET melt can have better fluidity, thereby realizing low-temperature production of PET sheets, thereby reducing energy loss in its production process and improving the energy saving of the production process;
[0054] At the same time, the polyethylene wax in the component has excellent lubrication in the molten state, and can form a lubricating layer between PET molecular chains to reduce internal friction; the lubricating layer reduces the friction resistance between the molecular chains, so that the PET melt has better fluidity at a lower temperature; and the polyethylene wax can effectively reduce the viscosity of the PET melt, promote the slippage of the molecular chain, improve the fluidity, further improve the fluidity of the PET melt, and can further improve the quality of the PET sheets produced under low temperature conditions;
[0055] Since the addition of plasticizers and polyethylene wax to the main layer 1 will reduce the rigidity and strength of the molded PET material, resulting in a decrease in the mechanical properties of the finished sheet, in this scheme, a reinforcement layer 2 is provided in the two main layers 1. By providing the reinforcement layer 2, the strength of the finished sheet is increased, thereby reducing the energy consumption in the sheet production process while ensuring that the sheet's own performance is maintained.
[0056] The body layer 1 further comprises 3-8 parts by weight of methyl methacrylate-butadiene-styrene copolymer.
[0057] When working, MBS (methyl methacrylate-butadiene-styrene copolymer) copolymer has a lower melt viscosity, and can reduce the viscosity of the overall melt and improve fluidity after mixing with PET; secondly, the molecular structure of MBS contains a flexible butadiene part, which increases the flexibility of the molecular chain of the blend, making PET easier to flow at a lower temperature; furthermore, MBS, as a modifier, forms a blending system with PET with good miscibility, and the modified material has better processing properties, so it can enhance the low-temperature fluidity of the PET melt, further reduce the temperature in its production process, and thus improve its energy-saving performance.
[0058] At the same time, the butadiene component in the MBS copolymer is elastic and can effectively absorb impact energy, thus improving the impact resistance of the material. This toughening effect allows the material to maintain good toughness even at low temperatures, reducing the risk of brittle fracture; MBS can improve the surface gloss and transparency of the material, improve the appearance quality, and make the product more competitive in the market. Especially in applications requiring high transparency and high gloss, such as transparent packaging and optical components, the addition of MBS has a significant effect.
[0059] The reinforcing layer 2 is made of the following raw materials in parts by weight: 80-100 parts of PET resin, 2-3 parts of glass fiber, 1-2 parts of nano silicon dioxide and 0.5-0.8 parts of polycarbonate.
[0060] The glass fiber is dispersed in the PET matrix, which can share the load applied by the outside world and reduce the stress concentration of the matrix, thereby improving the strength and rigidity of the composite material; at the same time, the good interface bonding can effectively transfer stress, so that the glass fiber and the PET matrix can bear the load together, and enhance the overall performance of the material;
[0061] Glass fiber can hinder the expansion of cracks. When encountering fibers, cracks will deflect and bifurcate, thereby dissipating more energy and increasing the toughness and impact resistance of the material. Fiber bridging: During the crack expansion process, the fiber plays a bridging role, slowing down the crack expansion speed and improving the fracture toughness of the material.
[0062] Glass fiber itself has a high elastic modulus. When mixed with the PET matrix, it can significantly improve the elastic modulus and hardness of the composite material.
[0063] The added nano-silicon dioxide particles can fill in between the PET molecular chains, increase the density of the material, reduce the free volume between the molecular chains, thereby improving the strength and rigidity of the material; can fill in between the PET molecular chains, increase the density of the material, reduce the free volume between the molecular chains, thereby improving the strength and rigidity of the material;
[0064] The added glass fiber provides macroscopic mechanical strength, and nano-silica improves the rigidity and strength of the matrix at the micro and nano scales, thereby achieving a better reinforcement effect; the thermal conductivity of glass fiber and nano-silica helps to dissipate heat evenly and prevent local overheating, thereby improving its stability during thermal processing and the stability of the finished material.
[0065] like Figure 1 As shown, the PET sheet further includes a UV coating 3, which is disposed on the surface of the main body layer 1 and has a thickness of 0.05-0.1 mm.
[0066] During the preparation of the main layer 1, plasticizers and flow modifiers are added, which will reduce the weather resistance of PET and make the PET sheet prone to aging and discoloration when used outdoors. Therefore, a layer of UV coating 3 is coated on the surface of the plate to increase the weather resistance of the PET sheet when used outdoors, improve the energy saving of the product while ensuring its weather resistance, thereby improving the application value of the product.
[0067] A method for producing energy-saving polyester PET sheets comprises the following steps:
[0068] S1: Preparation of body layer 1: half of the PET resin particles in the designed ratio are mixed with dioctyl phthalate and polyethylene wax, and heated to 220-230° C. to melt; then the remaining PET resin particles are added while stirring until all are melted; then methyl methacrylate-butadiene-styrene copolymer, hindered phenol antioxidant and zinc stearate are added and mixed evenly to obtain a melt of body layer 1;
[0069] S2: Preparation of reinforcing layer 2: All the designed amount of PET resin particles are heated to 220-230°C to make them in a molten state, and then nano-silicon dioxide is added thereto, and after being stirred evenly, glass fiber is added thereto and stirred evenly, and then polycarbonate is added thereto and stirred for 10-20 seconds to obtain a molten body of reinforcing layer 2;
[0070] S3: extrusion molding, the molten body layer 1 and the reinforcing layer 2 are respectively put into the extruder, and the extruder is operated to extrude them into sheets, and then cooled to form sheet-like semi-finished products;
[0071] S4: bonding and molding; the temperature of the main body layer 1 to be extruded is reduced to 60-80 degrees Celsius, and the temperature of the reinforcing layer 2 to be extruded is reduced to 100-120 degrees Celsius, and then the interface adhesive is sprayed on one side of the reinforcing layer 2, and then the main body layer 1 is adhered to the reinforcing layer 2, and then the pressure is maintained for 30 minutes, and the spraying and bonding processes are repeated to complete the bonding of the main body layer 1 on the other side;
[0072] S5: Surface treatment: anti-aging treatment is performed on the surface of the sheet after the main body layer 1 and the reinforcement layer 2 are adhered.
[0073] The following steps are also included:
[0074] Dry the raw materials, spread the PET particles evenly inside the vacuum dryer, and dry them at 120℃ for 30 minutes;
[0075] Raw material testing: take samples of the dried raw materials and use a moisture tester to test their moisture content. If the moisture content does not exceed 0.005%, it can be put into use, otherwise it will be dried again.
[0076] Raw materials are removed from the environment by putting the raw materials with qualified moisture content into the electrostatic dust removal equipment to remove the tiny dust impurities on the surface and complete the pretreatment of the PET granule raw materials.
[0077] Polyester materials such as PET are prone to hydrolysis during high-temperature processing, which leads to molecular chain breakage, reduced molecular weight, and thus affects the quality of PET finished products. Therefore, by removing moisture, hydrolysis can be prevented, the molecular weight of the material can be maintained, and the mechanical properties and chemical stability of the material can be ensured. Secondly, moisture will turn into steam at high temperatures, affecting the fluidity and uniformity of the melt. After dehydration, the raw materials in the molten state have better fluidity, which helps to improve processing performance and product quality. Furthermore, moisture will form bubbles during processing, resulting in defects on the surface of the finished product such as pores and flow marks. Removing moisture can avoid these defects, ensure the smoothness and uniformity of the finished product surface, and improve the appearance quality.
[0078] The anti-aging treatment of the sheet surface comprises the following steps:
[0079] Surface roughening: use a grinding head with a mesh size of 800 or above to grind the PET surface, and then clean the surface;
[0080] Spray the UV layer, evenly apply the UV coating on the polished sheet surface, and then wait for the sheet surface to dry naturally;
[0081] Apply UV coating by brushing. After the surface of the sheet is dry, apply UV coating 3 by brushing on the surface;
[0082] Curing treatment uses ultraviolet rays to irradiate the coating so that it cures quickly to form an anti-aging layer on the surface.
[0083] Since the surface smoothness of the PET sheet will decrease after grinding, and spraying often cannot solve the problem of surface smoothness, and directly applying the UV coating by coating often leads to low bonding strength, so spraying is first used for primer, so that a small amount of UV material is combined with the main layer 1, and then coating is used to solve the problem of surface smoothness, thereby improving the quality of the product.
[0084] In step S4, before the main body layer 1 and the reinforcement layer 2 are bonded together, a 200-mesh grinding head is used to grind the bonding surface of the main body layer 1 and the reinforcement layer 2; and the thickness of the interface adhesive is not less than 2 mm.
[0085] By grinding the bonding surface, the bonding area of the bonding surface can be increased, thereby increasing the bonding strength and improving the integrity of the produced sheet. After measurement, the difference between the protrusions and grooves on the surface after grinding with a 200-mesh grinding head is generally 0.4-1mm. By controlling the thickness of the interface glue, it can be ensured that the main layer 1 and the reinforcement layer 2 after bonding can achieve better bonding strength and better flatness.
[0086] The interface adhesive is a single-component polyurethane adhesive.
[0087] Polyurethane adhesive has good flexibility and weather resistance, and can improve the integrity of the sheet when used for interface bonding; at the same time, single-component polyurethane adhesive is more convenient to use, thereby improving the simplicity of the process.
[0088] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. An energy-saving polyester PET sheet, characterized in that: It comprises a main body layer (1), a reinforcement layer (2) is arranged between two main body layers (1), and the reinforcement layer (2) is bonded to the main body layer (1); The main body layer (1) is made of the following raw materials in parts by weight: 80-100 parts of PET resin, 2-5 parts of dioctyl phthalate, 0.5-1 part of polyethylene wax, 0.1-0.3 parts of hindered phenol antioxidant and 0.2-0.5 parts of zinc stearate.
2. The energy-saving polyester PET sheet according to claim 1, characterized in that: The invention also comprises 3-8 parts by weight of methyl methacrylate-butadiene-styrene copolymer.
3. The energy-saving polyester PET sheet according to claim 2, characterized in that: The reinforcing layer (2) is made of the following raw materials in parts by weight: 80-100 parts of PET resin, 2-3 parts of glass fiber, 1-2 parts of nano silicon dioxide and 0.5-0.8 parts of polycarbonate.
4. The energy-saving polyester PET sheet according to claim 3, characterized in that: It also comprises a UV coating (3), wherein the UV coating (3) is arranged on the surface of the main body layer (1) and has a thickness of 0.05-0.1 mm.
5. A method for producing energy-saving polyester PET sheets, applicable to the polyester PET described in any one of claims 1 to 4, characterized in that: The steps include: S1: Preparation of the main body layer (1), wherein half of the PET resin particles in the designed ratio are mixed with dioctyl phthalate and polyethylene wax, and then heated to 220-230° C. to melt; then the remaining PET resin particles are added while stirring until all of them are melted; then methyl methacrylate-butadiene-styrene copolymer, hindered phenol antioxidant and zinc stearate are added and mixed uniformly to obtain a molten body of the main body layer (1); S2: Preparation of reinforcing layer (2); heating all the designed amount of PET resin particles to 220-230° C. to make them in a molten state, then heating nano-silicon dioxide therein, adding glass fiber therein after stirring evenly, and stirring evenly, then adding polycarbonate therein and stirring for 10-20 seconds to obtain a molten body of reinforcing layer (2); S3: extrusion molding, the molten main body layer (1) and the reinforcing layer (2) are respectively put into an extruder, and the extruder is operated to extrude them into sheets, and then cooled to form a sheet-like semi-finished product; S4: bonding and molding; the temperature of the main body layer (1) to be extruded is reduced to 60-80 degrees Celsius, and the temperature of the reinforcing layer (2) to be extruded is reduced to 100-120 degrees Celsius, and then the interface adhesive is sprayed on one side of the reinforcing layer (2), and then the main body layer (1) is adhered to the reinforcing layer (2), and then the pressure is maintained for 30 minutes, and the spraying and bonding steps are repeated to complete the bonding of the main body layer (1) on the other side; S5: Surface treatment, anti-aging treatment is performed on the surface of the sheet material after the main body layer (1) and the reinforcement layer (2) are adhered.
6. The method for producing an energy-saving polyester PET sheet according to claim 5, characterized in that: The following steps are also included: Dry the raw materials, spread the PET particles evenly inside the vacuum dryer, and dry them at 120℃ for 30 minutes; Raw material testing: take samples of the dried raw materials and use a moisture tester to test their moisture content. If the moisture content does not exceed 0.005%, it can be put into use, otherwise it will be dried again. Raw materials are removed from the environment by putting the raw materials with qualified moisture content into the electrostatic dust removal equipment to remove the tiny dust impurities on the surface and complete the pretreatment of the PET granule raw materials.
7. The method for producing an energy-saving polyester PET sheet according to claim 6, characterized in that: The sheet surface anti-aging treatment comprises the following steps: Surface roughening: use a grinding head with a mesh size of 800 or above to grind the PET surface, and then clean the surface; Spraying UV coating (3), evenly coating the UV coating on the polished surface of the sheet, and then waiting for the surface of the sheet to dry naturally; Applying UV coating (3) by brushing, after the surface of the sheet material is dry, applying UV coating (3) by brushing on the surface of the sheet material; Curing treatment uses ultraviolet rays to irradiate the coating so that it cures quickly to form an anti-aging layer on the surface.
8. The method for producing an energy-saving polyester PET sheet according to claim 7, characterized in that: In step S4, before the main body layer (1) and the reinforcing layer (2) are bonded together, a 200-mesh grinding head is used to grind the surface where the main body layer (1) and the reinforcing layer (2) are bonded; the thickness of the interface adhesive is not less than 2 mm.
9. The method for producing an energy-saving polyester PET sheet according to claim 8, characterized in that: The interface adhesive is a single-component polyurethane adhesive.